Effects of different stretching methods on speed, jump, flexibility and upper extremity performance in wrestlers - Ari, Y. (Kinesiologia Slovenica, 2021)
The aim of this study is to investigate the acute effects of different stretching methods on acceleration, vertical jump (CMJ), flexibility and upper extremity performance of young wrestlers. 8 young female wrestlers (15.37 ± 1.06 years; 162.46 ± 4.12 cm and 57.47 ± 6.41 kg) participated in the study voluntarily. Stretching methods were divided into five groups: control (no stretching), static, dynamic, static + dynamic and dynamic + static. The findings showed faster speed performance after control (p = .012; ?2 = 0.57), dynamic stretching (p = .050; ?2 = 1.11) and static + dynamic combined stretching (p = .043; ?2 = 0.96) compared to static stretching; and there is a statistically significant positive difference according to the test averages after dynamic stretching (p = .050; ?2 = 0.91) compared to dynamic + static combined stretching (p<0.05). Vertical jump performance, according to the control warming up, a statistically significant difference has been found according to the test averages after dynamic stretching (p = 041; ?2 = 1.17) and static + dynamic combined stretching (p = .043; ?2 = 1.07). No difference was found in flexibility and medicine ball throwing performances according to different stretching protocols (p>0.05). It was determined that the acute effect of static stretching had a negative effect on acceleration performances and dynamic stretching caused an increase in jump performance. This study suggests that dynamic and static + dynamic stretching can be used in young wrestlers to provide better performance in acceleration and jumping skills during warm-up sessions.